2021
DOI: 10.1038/s41598-021-88125-7
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of lithosphere–atmosphere coupling for seismic events

Abstract: Significant evidence of ionosphere disturbance in connection to intense seismic events have been detected since two decades. It is generally believed that the energy transfer can be due to Acoustic Gravity Waves (AGW) excited at ground level by the earthquakes. In spite of the statistical evidence of the detected perturbations, the coupling between lithosphere and atmosphere has not been so far properly explained by an accurate enough model. In this paper, for the first time, we show the result of an analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Finally, it is worth noticing that the variation of f * does not show any dependence on earthquake magnitude (not shown). Such result agrees with Carbone et al [15], who demonstrated that the emission of a non-evanescent AGW, generating FLR variation, does not depend on the individual earthquake parameter alone, but on both the combination of the length of the fault, the PGA, the time duration of the EQ, etc (see dispersion relation in Carbone et al [15]), and the local atmospheric scale height.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Finally, it is worth noticing that the variation of f * does not show any dependence on earthquake magnitude (not shown). Such result agrees with Carbone et al [15], who demonstrated that the emission of a non-evanescent AGW, generating FLR variation, does not depend on the individual earthquake parameter alone, but on both the combination of the length of the fault, the PGA, the time duration of the EQ, etc (see dispersion relation in Carbone et al [15]), and the local atmospheric scale height.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, in the case of the absence of a co-seismic AGW emission, no possible f * variations can be detected (10 case event, see Table 1). Such a hypothesis is confirmed by Carbone et al [15], showing that the atmospheric fluctuations excited by a generic seismic event on the top of the first layer of the atmosphere can be evanescent. In fact, depending on the characteristic parameters of the EQ (length of the fault, peak ground acceleration strong time duration and so on), a the propagation of the AGW up to the ionosphere can be prevented.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations